Synthesis, characterization and evaluation of a carbazolyl-BODIPY as a fluorimetric chemosensor for F- - Pinto, Sónia C. S. (2022)
BODIPY dyes have received great attention in the last few years as optical chemosensors since they can recognize metal ions in solutions through optical signals (colorimetric and/or fluorimetric). In this context, our research group reports the synthesis of a carbazolyl-BODIPY derivative and its respective characterization by 1H NMR spectroscopy and mass spectrometry. Furthermore, a preliminary study of the chemosensory capacity of this BODIPY derivative was carried out in acetonitrile solution in the presence of several anions and a highly selective fluorimetric response was obtained for F-.